Best Paper Award (Oral Presentation) by IBA-IFIBiop 2022 - Koutinas, Michalis (My University, 2026)
The Ph.D. student Panayiota Karanicola was awarded the Best Paper Award (Oral Presentation) by IBA-IFIBiop 2022 that was held in Kaohsiung (Taiwan) for her work in the development of citrus processing waste-based biorefineries.
Keywords: Sciences